2009
DOI: 10.1128/aac.00400-09
|View full text |Cite
|
Sign up to set email alerts
|

AFN-1252, a FabI Inhibitor, Demonstrates a Staphylococcus-Specific Spectrum of Activity

Abstract: AFN-1252, a potent inhibitor of enoyl-acyl carrier protein reductase (FabI), inhibited all clinical isolates of Staphylococcus aureus (n ‫؍‬ 502) and Staphylococcus epidermidis (n ‫؍‬ 51) tested, including methicillin (meticillin)-resistant isolates, at concentrations of <0.12 g/ml. In contrast, AFN-1252 was inactive (MIC 90 , >4 g/ml) against clinical isolates of Streptococcus pneumoniae, beta-hemolytic streptococci, Enterococcus spp., Enterobacteriaceae, nonfermentative gram-negative bacilli, and Moraxella c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 6 publications
3
75
0
Order By: Relevance
“…This specific antistaphylococcal inhibitor of FabI had MIC values of Յ0.12 g/ml against all clinical isolates of S. aureus (n ϭ 502) and Staphylococcus epidermidis (n ϭ 51) tested, including methicillin-resistant strains. Poor activity was reported against streptococci, enterococci, and Gram-negative isolates, with MIC 90 values of Ͼ4 g/ml (216). Biochemical, structural, and microbiological studies confirmed that fatty acid biosynthesis was the killing target for the compound (217).…”
Section: Fatty Acid Synthesis Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…This specific antistaphylococcal inhibitor of FabI had MIC values of Յ0.12 g/ml against all clinical isolates of S. aureus (n ϭ 502) and Staphylococcus epidermidis (n ϭ 51) tested, including methicillin-resistant strains. Poor activity was reported against streptococci, enterococci, and Gram-negative isolates, with MIC 90 values of Ͼ4 g/ml (216). Biochemical, structural, and microbiological studies confirmed that fatty acid biosynthesis was the killing target for the compound (217).…”
Section: Fatty Acid Synthesis Inhibitorsmentioning
confidence: 98%
“…Scientists from Affinium Pharmaceuticals have described an iterative structure-guided chemistry program targeting FabI from S. aureus (214,215) from which they subsequently identified AFN-1252, a 3-methylbenzofuran linked to an oxotetrahydronaphthyridine by an N-methylpropenamide (216) (Fig. 6, compound 4).…”
Section: Fatty Acid Synthesis Inhibitorsmentioning
confidence: 99%
“…The Affinium clinical candidate AFN-1252 (Fig. 4F), which is closely related to its GSK progenitors, is staphylococcus specific in spectrum and has no demonstrable S. pneumoniae or S. pyogenes activity (184). No data on resistance selection by the GSK or Affinium FabI inhibitors are available.…”
Section: Single-enzyme Targets Of Novel Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…AFN-1252 is a potent and selective inhibitor of FabI that has no known off-target effects (20,24,36,37). AFN-1252 inhibits the growth of bacteria with a single essential FabI, including intracellular pathogens (18,20,24,38), but is ineffective against bacterial genes encoding the other enoyl-acyl carrier protein reductase isoforms (39). These data, coupled with the observation that S. aureus accD mutants are refractory to AFN-1252 (14), show there is little or no off-target toxicity of this drug.…”
Section: Resultsmentioning
confidence: 99%